Flypaper Effect Pada Dana Alokasi Umum, Dana Bagi Hasil Dan Pendapatan Asli Daerah Terhadap Belanja Daerah Pemerintah Provinsi Di Indonesia - Abrar, Naufal Muhammad Fajari; Masnila, Nelly; Dwitayanti, Yevi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2024)
Examining how the Flypaper Effect, the General Allocation Fund, the Revenue Sharing Fund, and Regional Original Income affect regional expenditure in Indonesian provinces was the primary goal of this study. The researchers in this study used purposive sampling to choose 22 out of 38 provinces in Indonesia for their investigation. The research included the years 2019 through 2022. The investigation's secondary data sources were compiled using the documentation technique. Data from the "Provincial Government Financial Report Audit Results" is specifically referenced in the budget realization report. For further information, see the official website at http://e-ppid.bpk.go.id. The multiple regression analysis method employed in this research is IBM SPSS 26. General allocation, revenue sharing, and regional original income all have a role in shaping regional spending, according to the research. Lower coefficients are associated with local revenue compared to the General Allocation Fund and Revenue Sharing Fund. Finally, the Flypaper Effect has an impact on the provincial governments of Indonesia.